(3EOGQI GdefXeGJ GdMchejIs - (3Ydj(B, (3TQjas ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2003)
(3GdOhdI hGdEOGQI hGdefXeGJ, HjFI GdEOGQI GdYGeI, GdYedjGJ GdEOGQjI hGdJfXjejI, GdEOGQI GdYGeI GdebGQfI, GdJchjf GdJfXjej ddefXeGJ GdYGeI, JUfja GdefXeGJ GdYGeI, GdSdWGJ GdYGeI, GdEOGQI GdYGeI GdebGQfIs
Keywords: (3GdEOGQIs; (3GdEOGQI GdMchejIs; (3GdEOGQI GdYGeIs